Bioprinted keratinocyte and stem cell-laden constructs for skin tissue engineering - Bettendorf, Eva; Schmid, Rafael; Horch, Raymund E.; Kengelbach-Weigand, Annika; Kulicke, Yvonne; Schrüfer, Stefan; Schubert, Dirk W.; Lamberger, Zan; Stahlhut, Philipp; Lang, Gregor; Sörgel, Celena (International Journal of Bioprinting, 2024)
Treating large-scale skin wounds remains a significant therapeutic challenge, often due to insufficient autologous material for complete coverage. Recent advances in biofabrication offer a solution with reproducible and precise large-scale production. Herein, this study aims to evaluate the feasibility of biofabrication and develop a customized three-dimensional (3D) bioprinted skin construct containing immortalized HaCaT keratinocytes and adipose-derived stem cells (ADSCs). Keratinocytes were cultured in various hydrogels (e.g., containing alginate [Alg], fibrin [Fib], collagen, gelatin [Gel], gelatin methacryloyl [GelMA], hyaluronic acid [HA], and a pre-fabricated collagen-elastin-matrix) for 7 days. The metabolic activity of cultured keratinocytes was then evaluated during the co-cultivation of HaCaT and ADSCs in a transwell model. The metabolic activity in all groups increased over the experimental period. Alg/HA/Gel and GelMA hydrogels demonstrated good printability and high diffusion rates. There was no significant difference in pore size between all hydrogels. Based on the results of printability and diffusion assays, as well as scanning electron microscopy (SEM) and rheological measurements, Alg/HA/Gel and GelMA hydrogels were selected for the bioprinted 3D model. Fib hydrogel was integrated into the biofabricated constructs for its excellent metabolic activity in the transwell model. Hydrogel stability, cell survival, and metabolic activity in bioprinted 3D models containing keratinocytes and ADSCs were evaluated over 14 days. On day 14, metabolic activity and live cell count within the bioprinted constructs of the co-cultured groups were significantly higher compared to day 1. The biofabricated GelMA constructs displayed higher cell viability than Alg/HA/Gel constructs. Additionally, to evaluate cell migration out of the constructs, the metabolic activity and viability of the cells on the well bottom were examined. After 14 days, an average of 50% of the well bottom was covered by HaCaT cells, which were initially printed in co-culture into the constructs. These findings indicate that GelMA constructs containing keratinocytes and ADSCs may offer a promising therapeutic option in the treatment of large chronic wounds.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Bioprinting; Hydrogel; Keratinocytes; Skin substitution; Stem cells; Wound healing

In Vivo Vascularization of Cell-Supplemented Spider Silk-Based Hydrogels in the Arteriovenous Loop Model - Osterloh, Justus; Heltmann-Meyer, Stefanie; Trossmann, Vanessa T.; Cai, Aijia; Kulicke, Yvonne; Terörde, Klara; Sörgel, Celena; Lang, Isabell; Wajant, Harald; Scheibel, Thomas; Fey, Tobias; Steiner, Dominik; et al. (Biomimetics, 2025)
The goal of reconstructive surgery in treating tissue defects is to achieve a stable reconstructive outcome while minimizing donor site morbidity. As a result, tissue engineering has emerged as a key focus in the pursuit of this goal. One approach is to create a tissue container that can be preconditioned and later transplanted into the defect area. The characteristics of the matrices used in the tissue container are critical to this approach’s success. Matrices generated with recombinant, functionalized spider silk (eADF4(C16)-RGD) have been reported to be biocompatible and easy to vascularize. However, the effect of exogenously added proangiogenic cells, such as endothelial cells (T17b), on the vascularization process of matrices generated with this hydrogel in vivo has not been described yet. In this study, we implanted arteriovenous (AV) loop containers filled with a spider silk hydrogel consisting of an eADF4(C16)-RGD matrix and encapsulated, differentiated endothelial T17b cells producing the reporter protein TNFR2-Fc-Flag-GpL. The histological and µCT analyses revealed spontaneous angiogenesis and fibrovascular tissue formation in the container at 2 and 4 weeks post-implantation. The reporter protein was detected after 4 weeks. No severe immune response was observed. Altogether, this study demonstrates that cell-supplemented recombinant spider silk is a highly promising hydrogel to produce matrices for tissue engineering applications.
CRIS-Team Scopus Importer:2025-03-14
Keywords: recombinant spider silk; reconstructive surgery; tissue engineering; vascularization